KORELASI PERILAKU KORUPSI KEPALA DAERAH DENGAN PILKADA LANGSUNG - Iza Rumesten (Faculty of Law, Universitas Jenderal Soedirman, 2014)
The increase of regional chiefs who had been imprisoned for corruption makes Kemendagri (The Ministry of Home Affairs) issue a discourse to restore local elections to Parliament. Nevertheless, this discourse will not support the process of democracy in Indonesia. Instead, it pulls backwards into the era of the new order and causes any corrupt practices to move to other parties, from bribing people into Parliament. Hence what issued by the ministry is not the best solution. This paper discusses about how the correlation between direct local election and corruption behavior of regional chiefs. The solution to overcome this is done by changing the system ranging from political parties to the intensive monitoring involving active community over all government policies in regional level and the application of legal supremacy along with equality before the law firmly against corruption by impoverishment.Key words: politic of law, corruption, regional election